Myopenia and precision (P4) medicine. Issue 6 (24th September 2017) - Morley, John E.; Anker, Stefan D.
Abstract: Precision (P4) medicine represents a new medical paradigm that focuses on Personalized, Predictive, Preventive and Participatory approaches. The P4 paradigm is particularly appropriate for moving the care of persons with myopenia forward. Muscular dystrophies are clearly a set of genetically different diseases where genomics are the basis of diagnosis, and genetic modulation via DNA, oligonucleotides and clustered regularly interspaced short palendronic repeats hold great potential for a cure. The utility of personalized genomics for sarcopenia coupled with utilizing a predictive approach for the diagnosis with early preventive strategies is a key to improving sarcopenic outcomes. The importance of understanding different levels of patient enthusiasm and different responses to exercise should guide the participatory phase of sarcopenic treatment. In the case of cachexia, understanding the effects of the different therapies now available through the P4 approach on muscle wasting is a key to management strategies.